Matrine Enhances the Pathogenicity of Beauveria brongniartii Against Spodoptera litura (Lepidoptera: Noctuidae) - Wu, Jianhui; Yu, Xintong; Wang, Xiaoshuang; Tang, Liangde; Ali, Shaukat (Frontiers in Microbiology, 2019)
The repetitive application of pesticides at high doses against Spodoptera litura Fabricius has resulted in development of pesticide resistance and harmful effects to natural environmental. Hence, finding alternate pest control strategies such as entomopathogenic fungi or their application in combination with other natural chemicals is need of the hour to solve the above mentioned problems. This study presents the toxic effects of Beauveria brongniartii and matrine (individual or in combination with each other) against tobacco cutworm (Spodoptera litura). Different matrine treatments caused a dose dependent increase in S. litura mortality at different time intervals. The biological parameters of B. brongniartii (germination rate and average daily mycelia growth) were not inhibited by different matrine treatments. Different conidial concentrations of B. brongniartii caused significantly different mortalities of 2nd instar S. litura larvae at different time intervals. Different combined treatments of B. brongniartii and matrine showed a significant synergistic effect against S. litura under laboratory and semi field conditions. The current findings showed a strong synergistic action for combined application of B. brongniartii and matrine against S. litura. Our results will provide base line information on combined application of entomopathogenic fungi and natural chemicals in integrated pest management programs against S. litura.